The Unintended Consequences on Crime of "Pennies from Heaven" - Daniel Montolio (Inter-American Development Bank (IDB), 2016)
This paper examines how an infrastructure investment policy, implemented nationwide at the local level, has affected local crime rates. This policy, developed in the wake of the global recession of 2008-09, was designed to boost local economies through job creation. Using monthly figures from the Spanish region of Catalonia's more than 900 municipalities, the paper exploits geographic and time variation in the Spanish Ministry of Public Administration's random approvals of local investment policies, to estimate their impact on both (un)employment and crime. The combination of difference-in-differences and IV estimates makes it possible to precisely assess both the size and timing of the policy's impact on the local labor market and on municipal-level crime rates. While the policy apparently did not tackle the economic recession over the long run, local public finances did experience a boost over the short term, resulting in a temporary reduction in local unemployment rates (as legally required by the policy), as well as a significant drop in crime rates.
hdl:11319/7431
Keywords: K42; R53; H54; J40; 330; Crime; Unemployment; Local investment Policies; Local economic development